Avaliação das Farinhas de Peixe e Pena, no Confinamento de Bezerros Leiteiros Desmamados, Através de Dietas Calculadas em Termos de Proteína Bruta ou de Proteína Metabolizável - Oliveira, Marcus Vinicius Morais de; Sanchez, Luis Maria Bonecarrère; Vargas Júnior, Fernando Miranda [UNESP]; Perez, Juan Ramón Olaquiaga; Pires, Cleber Cassol; Haygert, Ione Maria Pereira; Frizzo, Adriana; Lana, Rogério de Paula (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2002)
The objectives of this work were to evaluate three protein sources - soybean meal, fish meal and feather meal - and two methods of calculation of rations - the calculated in terms of crude protein (CP), according to recommendations of NRC (1988); and the proposed by the AFRC (1993), and calculated in terms of metabolizable protein (MP) - through the performance of calves. The animals were confined and submitted to five diets, that varied only protein sources in its composition, thus discriminated: SM- Soybean Meal, FsM- Fish Meal, FeM- Feather Meal, FsMU- Fish Meal and Urea, and FeMU Feather Meal and Urea. A complete diet was supplied, composed of 40% of sorghum silage and 60% of concentrate. All treatments possessed about of 2.56 Mcal/kg DM of metabolizable energy, being the treatments SM, FsM and FeM calculated by the system of CP, with 18% of CP, and the treatments FsMU and FeMU, calculated by the system of MP, with 16.3% of CP and a same amount of metabolizable protein than the treatment SM, with 112.0 grams of MP/day. Individually, the treatments did not present significant differences (P > 0.05) in the final alive weight, in daily gain weight and in dry matter intake, having differences only in the feed:gain ratio. The best feed:gain ratio happened in the treatment FsM and the worst in the treatment FeMU. It is concluded that the MP method provides similar results to the method of CP. The treatments with fish meal provide larger weight gains, smaller intake and better feed:gain ratio than the treatments with feather meal, staying the treatment soybean meal with intermediary daily gain.
Evaluation of fish and feather meals for confined dairy calves weaned through diets calculated in terms of crude protein or metabolizable protein
Keywords: AFRC; feedlot; performance